Effect of convex tooth flank form deviation on the characteristics of transmission error of gears considering elastic deformation - Mohamad, E.N.; Komori, M.; Murakami, H.; Kubo, A.; Fang, S. (American Society of Mechanical Engineers (ASME), 2010)
The transmission error of gears is an important factor for power transmissions, particularly automotive. Consequently, a lot of research has been conducted on the gear transmission. However, in contrast, there remains relatively little research clarifying the characteristics of gear transmission error and its relationship to the tooth flank form. The authors have proposed a general model for tooth meshing between gears. This expresses the transmission error theoretically from a quasi-infinite elastic model, which is composed of springs with stiffness specific to the gears. In this report, the influence of tooth flank form deviation on transmission error is further investigated by using this model. It is shown that the form of the ridge curve of the tooth flank form deviation greatly influences the actual contact ratio at the minimum point of peak-to-peak value of transmission error. The peak-to-peak value of transmission error is affected by the amplitude and the form of the ridge curve. [DOI: 10.1115/1.4002458]